British Policy and the Communist Insurrection in Malaya 1946-1957: The Success of the British Struggle Against the First Communist Threat After the Second World War - Zulhilmi, Paidi (1996)
One of the most important events in the history of Malaya under the British Colonisation was the Communist insurrection. The insurrection was one of the toughest threats the British Imperial power had faced in Malaya since 1824 when they officially started their colonisation in the peninsula. The insurrection, which resulted in Emergency Rule was the first British struggle after the end of Second World War. It was a great challenge for the British Colonial policy to put down the insurrection, stop the spread of Communism and at the same time prepare the multi-racial society founded by the British pre-war policy for self government. It took the efforts of three successive British High Commissioners, Sir Edward Gent, Sir Henry Gurney and Sir Gerald Templer, before the insurrection could be slowed and the country was granted the independence.